2022
DOI: 10.1021/jacs.1c11150
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Optoelectronic Performance by Regulating Exciton Behaviors in a Porous Semiconductive Metal–Organic Framework

Abstract: Exciton behaviors including exciton formation and dissociation dynamics play an essential role in the optoelectronic performance of semiconductive materials but remain unexplored in semiconductive metal–organic frameworks (MOFs). Herein, we reveal that the exciton behaviors in semiconductive MOFs can be regulated by framework–guest interactions, a feature often not achievable in traditional inorganic or organic semiconductors. Incorporation of the electron-deficient molecule within the pores of a terbium-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 54 publications
4
38
0
Order By: Relevance
“…16 Metal-organic frameworks (MOFs) are outstanding candidates for fluorescence sensors because of their adjustable structures, modified ligands and active sites, high surface areas and tunable physicochemical properties. [17][18][19][20] In recent years, small molecules, ions, solvents, gases, biomolecules, pH, temperature and other types of analytes have been efficiently detected by MOF-based fluorescent sensors. [21][22][23][24][25][26][27][28] The detection mechanism based on MOFs is also attributed to the electron/ energy transfer, which is closely related to the weak interactions (p-p stacking or hydrogen bonds) between the MOFs and the analytes.…”
Section: Introductionmentioning
confidence: 99%
“…16 Metal-organic frameworks (MOFs) are outstanding candidates for fluorescence sensors because of their adjustable structures, modified ligands and active sites, high surface areas and tunable physicochemical properties. [17][18][19][20] In recent years, small molecules, ions, solvents, gases, biomolecules, pH, temperature and other types of analytes have been efficiently detected by MOF-based fluorescent sensors. [21][22][23][24][25][26][27][28] The detection mechanism based on MOFs is also attributed to the electron/ energy transfer, which is closely related to the weak interactions (p-p stacking or hydrogen bonds) between the MOFs and the analytes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that the optoelectronic efficiency of semiconductive MOFs can be bolstered by efficient framework-guest interaction. 315 In particular, it was shown that the incorporation of electron-deficient guest molecules in the pores of a Terbium-based MOF results in significant energy transfer and facilitates the conversion of Wannier-type excitons into Frenkel-type excitons.…”
Section: Excitons In Hybrid Materialsmentioning
confidence: 99%
“…As shown in Figure 3A, under X-ray irradiation, the photocurrent sharply changes to the range of 10 −9 −10 −8 A with an increase of 2 orders of magnitude compared to the leakage current under dark conditions, suggesting a significant charge transport in EAUCl. 31 Note that the photocurrent of D2 is slightly lower than that of D1, which is attributed to thickness-induced charge carrier loss. We further monitored the radiation stability of EAUCl.…”
mentioning
confidence: 95%